CRITICAL THINKING AND SCIENTIFIC APPROACH IN EFL CONTEXT: A LITERATURE REVIEW - Ansari, Ni Made Saraswati (CaLLs (Journal of Culture, Arts, Literature, and Linguistics), 2021)
Critical thinking should be encouraged in English as a Foreign Language learning based on a scientific approach. The present study reviews arguments, opinions, and previous studies on the implementation of scientific approaches in English as a Foreign Language classes for improving student's critical thinking. The review reveals that critical thinking skills cover three aspects: quick thinking, creative thinking, and analytical thinking. To improve the students’ critical thinking, teachers play a crucial role in the learning process using innovative learning models based on scientific approaches. Three learning models considered most useful for developing students' critical thinking are discovery learning, problem-based learning, and project-based learning. Through discovery learning, students learn new things by solving the problem and exploring. In problem-based learning, a contextual problem is given at the beginning of the lesson, not the content being discussed. The third, project-based learning, students learn by doing and being enthusiastic with all processes of learning. Since critical thinking skills are crucial for solving language learning problems and beyond, language learning should integrate linguistic contents with the cognitive skills and dispositions, dimensions of critical thinking.